Modernisasi Metode Pembelajaran Alquran Anak Usia Dini (Analisis Pergeseran Budaya; Kasus di Tpq An-Nahdiyyah Nganjuk) - Natsir, Ahmad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2017)
The development of technology and the opening of information, has influenced a number ofMuslim communities to change the existing educational system in Islamic institutions. TPQ(Taman Pendidikan Alquran) An-Nahdiyyah, which has students of the average age of earlychild, is also not spared from the development of a system. From the beginning of the Iqra'method (not based on the ratio of the number of students, the semester program, even theconferencing scoring system) now to the Ummi method with all the completeness of itsmanagement, the penetration of progress of the learning method begins to find a shift. Thisshift in the method of learning of the Qur'an is interesting to do a research study with theframework of Mike Featherstone, with the formulation of the problem as following conclusions;(1) Ummi method in learning the Qur'an has dominated in private Islamic institutions, there areat least three educational institutions of either MI, MTs, or MA who have applied Ummi learningmethod; (2) Ummi's aestheticization process is found in the results achieved, Ummi methodalumni are more able to read the Qur'an with the correct variety and tajwid; (3) the weakness ofthe reference system contained in the Iqra 'method makes this method gradually abandoned.